The impact of derivative use on firm risk and firm value. Evidence from South African non-financial firms - Mwangi, Edwin (Department of Finance and Tax, 2021)
This dissertation investigates the extent of derivatives use in South Africa. In addition, it examines the effect of derivatives use on firm risk and value. The dissertation is based on a sample of 91 South African non-financial firms listed on the FTSE/JSE Africa All Share Index on the JSE over the sample period 2012 to 2016. Firm risk is measured using total risk, systematic risk and unsystematic risk while the Tobin's Q is used as the proxy for firm value. The results of this dissertation show that 62% of firms included in this sample use derivatives. Foreign currency derivatives were the most commonly used as 80.3% of firms used them followed by interest rate derivatives at 46% and then commodity price derivatives at 21.8%. This dissertation provides evidence that the use of derivatives significantly reduces total risk and unsystematic risk. However, the use of derivative does not have an effect on systematic risk. The use of derivatives increases firm value although this increase is not statistically significant. Overall, this dissertation finds evidence of risk reduction related to derivative usage but fails to establish the value premium that is created by derivative use.